Increasing the Confidence of Generation Z Through Kalam Knowledge - Asgar Marzuki; Abdus Sami R Kasa; Ulla Navita Romadhoni (FKIP - Universitas Riau, 2026)
Generation Z faces significant challenges in maintaining religious faith amid the rapid flow of digital information, secularization, and moral relativism. These conditions often lead to spiritual crises and a declining understanding of Islamic creed among young Muslims. This study aims to analyze the role of Ilmu Kalam in strengthening Generation Z’s faith through rational and theological approaches. The research employs a literature review method, examining both classical and contemporary sources on Ilmu Kalam and its relevance to the intellectual characteristics of Generation Z. The findings reveal that the rational and argumentative principles of Ilmu Kalam provide logical and contextual religious understanding, addressing intellectual doubts while reinforcing faith. Furthermore, Ilmu Kalam plays a crucial role in developing a critical and moderate mindset without neglecting the essence of tawhid. The study concludes that revitalizing Ilmu Kalam in Islamic education and da’wah is essential to strengthen Generation Z’s religious conviction and identity in the modern era.